Semi-Aerobic Landfill System as Alternative Solution for Indonesian Landfill - Khaira Misrawati; Zaflis Zaim (Jurnal Ilmu Lingkungan, 2024)
Indonesia has been encountering pressing problems in managing municipal solid waste (MSW). According to data from the Ministry of Environment and Forestry (KLHK), up to 35.46% of landfills were run as open-dumping landfills until May 2022 because proper sanitary landfill concepts were not fully implemented and the condition of landfills in Indonesia is on the point of being overcapacity. With the development of landfill technology, the Ministry of Public Works is currently starting to develop other alternative landfill systems. From the general findings of this study, it can be concluded that the semi-aerobic landfill system is an available method to be used as an alternative solution for Indonesian landfills. This is based on the results of the SWOT matrix, which shows strategic factors derived from internal and external factors originating from previous studies and issues regarding landfills in Indonesia. The analysis of these factors shows that the semi-aerobic landfill system produces better performance by reducing the potential for environmental pollution of water and air and greenhouse gas emissions. The implementation of a semi-aerobic landfill system is a viable method to be used in developing countries.